Effectiveness of Academic Supervision by Principals in Improving Teacher Professionalism and Learning Quality - Hamdan Fathurrohman; Iskandar Mirza (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Academic supervision is a crucial instrument for school principals in enhancing teacher professionalism. This study aims to analyze the planning, implementation, and supporting as well as inhibiting factors of academic supervision at SMP Pasundan Tanjungsari and SMP Plus Persatuan Islam Tanjungsari. A qualitative approach with a comparative case study design was employed, using interviews, observations, and document analysis. The findings show that at SMP Pasundan, 78% of teachers felt actively involved in planning through collaborative forums, while at SMP Plus Persatuan Islam, 90% of decisions were made hierarchically by the principal. The implementation of clinical supervision at Pasundan improved teachers’ classroom management and technology integration skills (85% of teachers), whereas the directive approach at Persatuan Islam increased compliance with standards (92% of teachers met the minimum competency criteria) but was less effective in fostering pedagogical innovation. Supporting factors included budget allocation and religion-based mentoring, while key challenges were principals’ administrative burdens (35% of their time) and resistance from senior teachers (18% of cases). This study proposes an adaptive hybrid model of supervision that combines collaborative and directive approaches based on teachers’ professional competence and school context